MANAGERIAL PERSPECTIVES ON BUILDING MAINTENANCE THROUGH THE INTEGRATION OF NONCONVENTIONAL TECHNOLOGIES AND INNOVATIVE SOLUTIONS (Nonconventional Technologies Review, 2025)
Building maintenance is undergoing a profound evolution, thanks to the integration of innovative technological solutions. The use of drones equipped with optical and thermal sensors, capable of integrating RGB imaging with infrared thermography and generating elaborate 3D models, opens new perspectives for the diagnosis and optimization of buildings. This method is not limited to the rapid detection of hidden defects and monitoring of energy performance, but also leads to a reduction in costs and risks associated with conventional inspections. At the same time, by detecting energy losses and improving decision-making, RGB-T 3D technology contributes to extending the lifespan of buildings and reducing carbon emissions. The paper analyzes the transition from the visible to the infrared spectrum, practical scenarios for using drones in audits and maintenance processes, but also the current limitations of these tools. Finally, the potential of three-dimensional aerial thermography to become a key element in modern building maintenance management is highlighted, with direct advantages for sustainability and the development of a more efficient and environmentally responsible built environment
Keywords: : Innovative technologies; 3D thermography; Drone inspection; Building maintenance; Carbon emission reduction